Implementasi Metode Finger Painting dalam Peningkatan Kreativitas Anak Usia Dini di TK Islam Masa Depan Ketapang Desa Menceh Kecamatan Sakra Timur Tahun Ajaran 2021/2022 - Qusyairi, Lalu A. Hery; Nurmah, Nurmah (Lembaga Yasin AlSys, 2022)
A study entitled Implementation of the Finger Painting Method in Improving Early Childhood Creativity in the Future Islamic Kindergarten of Ketapang in the 2021/2022 Academic Year has been carried out. This study aims to increase the creativity of Early Childhood using the Finger Painting method. Children's creativity can be developed by doing a variety of interesting activities, the latest learning models, providing learning media that can attract children's attention in the learning process so as to make children more excited. This research is a Classroom Action Research (CAR) using qualitative methods. The research data were obtained by using observation and documentation techniques. The increase in the creativity of students is indicated by the increasing number of positive (yes) columns that are filled in for each indicator set. The research obtained is the indicator